2006
DOI: 10.1634/theoncologist.11-3-285
|View full text |Cite
|
Sign up to set email alerts
|

Nongastric Marginal-Zone B-Cell MALT Lymphoma: Prognostic Value of Disease Dissemination

Abstract: Learning ObjectivesAfter completing this course, the reader will be able to:1. Discuss the different modalities of disease dissemination in nongastric marginal-zone B-cell MALT lymphoma.2. Explain the rationale for using extensive staging in nongastric marginal-zone B-cell MALT lymphoma. Access and take the CME test online and receive 1 AMA PRA category 1 credit at CME.TheOncologist.com CME CME This material is protected by U.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
43
4
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 18 publications
7
43
4
4
Order By: Relevance
“…The mediastinal adenopathy designation in our patients could confer behaviour closer to nodal MZLs rather than MALT lymphoma, in accordance with a previous report [31]. Although there are conflicting results regarding the influence of dissemination on survival [1,32], an extrapulmonary location was not associated with a shorter PFS or overall survival in this series. Indeed, the impact of extensive evaluation at diagnosis, including bone marrow biopsy and endoscopic examination of the gastrointestinal tract, should be better evaluated in patients who cannot be cured by local therapy.…”
Section: Discussionsupporting
confidence: 90%
“…The mediastinal adenopathy designation in our patients could confer behaviour closer to nodal MZLs rather than MALT lymphoma, in accordance with a previous report [31]. Although there are conflicting results regarding the influence of dissemination on survival [1,32], an extrapulmonary location was not associated with a shorter PFS or overall survival in this series. Indeed, the impact of extensive evaluation at diagnosis, including bone marrow biopsy and endoscopic examination of the gastrointestinal tract, should be better evaluated in patients who cannot be cured by local therapy.…”
Section: Discussionsupporting
confidence: 90%
“…localized orbital, salivary gland and thyroid lymphoma, most frequently include radiotherapy as first-line therapy, whereas chemotherapy is administered for localized pulmonary lymphoma. 5 In case of multiorgan involvement, which can be expected in almost 50% of the patients, according to this study and others, 10,12,13 systemic therapy with either chemotherapy or chemotherapy in combination with rituximab could be a good treatment approach. Alkylating agents, fludarabine, cladribine and platinum compounds as single agents or in combination have been active with good response rates (i.e.…”
mentioning
confidence: 55%
“…Extranodal marginal zone B-cell lymphoma, a subtype of NHL, is the third most common form of NHL and it accounts for approximately 5% of NHL cases (4)(5)(6). It is histologically characterized by a heterogeneous cellular composition, including marginal zone or centrocytelike cells, monocytoid B cells, small lymphocytes, and plasma cells (7).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MZL is associated with chronic antigenic stimulation, either by autoantigen or pathogen, leading to the accumulation of lymphoid tissue in the involved organs (8,9). While the gastrointestinal tract is the most common site, approximately 5% of extranodal MZL is found in the lung (5,6). Extranodal marginal zone B-cell lymphoma can affect any age group of either sex.…”
Section: Discussionmentioning
confidence: 99%